2012
DOI: 10.5334/jbr-btr.92
|View full text |Cite
|
Sign up to set email alerts
|

A rare presentation of colonic duplication cyst: report of a case and review of the literature.

Abstract: Duplication cyst is an extremely rare congenital malformation of the alimentary tract. It occurs most often in the ileum, accounting for over 60% of cases followed by the jejunum and the duodenum (1). The colon is the least common site of enteric duplication. In fact, in a review of 495 alimentary tract duplications only 7% of the duplications involved the colon (2). To our knowledge less than 100 cases have been described in the published literature (3). Case reportWe present an unusual case of colonic duplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Structurally, they can be cystic in 80% and tubular in 20% of cases. Cystic duplications are not related to adjacent intestinal lumen whereas tubular lesions may be related to adjacent colonic lumen adjacent as in our case (17) . It has been reported that ectopic tissue is present in 25-30% of duplicated specimens and most common types of ectopic tissues are gastric followed by pancreatic tissue (6) .…”
Section: Discussionmentioning
confidence: 43%
“…Structurally, they can be cystic in 80% and tubular in 20% of cases. Cystic duplications are not related to adjacent intestinal lumen whereas tubular lesions may be related to adjacent colonic lumen adjacent as in our case (17) . It has been reported that ectopic tissue is present in 25-30% of duplicated specimens and most common types of ectopic tissues are gastric followed by pancreatic tissue (6) .…”
Section: Discussionmentioning
confidence: 43%
“…The radiologic examination of our case clearly showed the cystic structure of the mass in addition to the histopathological examination revealing that the cyst lumen was covered with the intestinal mucosa and that it was incorporated with the adjacent intestinal smooth muscle structure. Duplication cysts are typically not related to the adjacent intestinal lumen as observed in our case, whereas tubular lesions may be related to the colon [6].…”
Section: Discussionmentioning
confidence: 49%
“…There is a lack of unified diagnostic and treatment criteria for transverse colonic repetitive malformations. 12 cases were diagnosed using abdominal multirow CT ( 12 , 13 , 15 18 , 20 24 , 26 ), 8 cases using digitized barium enema colography ( 13 , 14 , 17 – 19 , 22 , 23 , 25 ), and colonoscopy in 4 cases ( 19 , 20 , 25 , 26 ), 8 cases using US ( 13 – 16 , 18 , 20 22 ) and 2 cases using plain X-ray ( 16 , 18 ). Because the symptoms of repeat transverse colon malformations in adults are mostly nonspecific, clinical diagnosis is difficult.…”
Section: Discussionmentioning
confidence: 99%